1992
DOI: 10.1039/c39920001668
|View full text |Cite
|
Sign up to set email alerts
|

η2-Benzyne and η1-benzylidene complexes of niobium with ancillary imido ligands

Abstract: Rare q2-benzyne and benzylidene complexes of niobium have been synthesised from [Nb(C5R5)(NR')C12] (R = H, Me; R' = 2,6-Pri2C6H3) via intermediate diphenyl and dibenzyl species and their molecular structures have been determined: these complexes are analogues of well-established zirconocene derivatives.Recently? we described a series of half-sandwich imido useful relationship since zirconocene reagents are widely complexes of niobium of the general type [Nb(C5R5)-exploited in organic synthesis2 and polymerisat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

1994
1994
2007
2007

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(38 citation statements)
references
References 25 publications
2
36
0
Order By: Relevance
“…[14, 15,16] We then turned to the Cp/imido ligand set, which had proved to be isolobal with the Cp 2 ancillary, [1,17] …”
Section: A C H T U N G T R E N N U N G (=Nme)a C H T U N G T R E N N mentioning
confidence: 99%
“…[14, 15,16] We then turned to the Cp/imido ligand set, which had proved to be isolobal with the Cp 2 ancillary, [1,17] …”
Section: A C H T U N G T R E N N U N G (=Nme)a C H T U N G T R E N N mentioning
confidence: 99%
“…The typical spectral pattern of the allyldimethylsilyl group consists of two high field signals observed as one singlet for both equivalent silicon methyl groups and one doublet for the methylene silicon-bound group, together with three low field signals appearing as two doublets for the olefinic methylene group and one multiplet due to the internal olefinic proton. The ring proton resonances are shifted upfield for imido complexes (5)(6)(7)(8) compared with the tetrachloro niobium derivative 1, whereas the resonances due to SiMe 2 , Si-CH 2 and olefinic CH@CH 2 protons of the dimethylsilylallyl group are shifted low field, the Si-CH 2 being the most sensitive signals. These displacements are related to the stronger r-p-donating character of the imido ligand, causing the metal to require less electron density from the aromatic ring.…”
Section: Structural Studiesmentioning
confidence: 94%
“…In this way, reaction of 1 with Li(C 5 unique component in 90% yield by a redistribution reaction when an equimolar mixture of 5 and 7 was heated in toluene at 120°C. The alkyl complexes 6-8 were isolated as waxy brown air sensitive solids, very soluble in all organic solvents including hexanes.…”
Section: Synthetic Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[5,7,9 -11,33 -35] We have demonstrated that half-metallocene-diene fragments of group 5 metals are isoelectronic and isolobal to metallocene fragments of group 4 metals. [36 -40] Figure 2 shows some typical alkylidene complexes of group 4 metals [41,42] and group 5 metals [43,44] with isoelectronic fragments. This review briefly describes our studies on the synthesis and characterization of benzylidene complexes of tantalum and their stereochemistry of the benzylidene moiety, which was tunable and was highly depending on the kinds of ancillary ligands such 1,3-butadiene (1), [45,46] 2,3-dimethyl-1,3-butadiene (6), [47] o-xylylene (7), [46] 1,4-diaryl-1,4-diaza-1,3-butadiene (8), [48] and 1,4-diaryl-1-aza-1,3-butadiene (9).…”
Section: Introductionmentioning
confidence: 99%